2019
DOI: 10.1186/s12864-019-6353-2
|View full text |Cite
|
Sign up to set email alerts
|

Protein expression profiles in Meishan and Duroc sows during mid-gestation reveal differences affecting uterine capacity, endometrial receptivity, and the maternal–fetal Interface

Abstract: BackgroundEmbryonic mortality is a major concern in the commercial swine industry and primarily occurs early in gestation, but also during mid-gestation (~ days 50–70). Previous reports demonstrated that the embryonic loss rate was significant lower in Meishan than in commercial breeds (including Duroc). Most studies have focused on embryonic mortality in early gestation, but little is known about embryonic loss during mid-gestation.ResultsIn this study, protein expression patterns in endometrial tissue from M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…Differences were tested for statistical significance USA). The detailed steps for enzymolysis and iTRAQ labeling have been described previously [5,9].…”
Section: Expression Level Validation By Qpcr (Quantitative-pcr)mentioning
confidence: 99%
See 1 more Smart Citation
“…Differences were tested for statistical significance USA). The detailed steps for enzymolysis and iTRAQ labeling have been described previously [5,9].…”
Section: Expression Level Validation By Qpcr (Quantitative-pcr)mentioning
confidence: 99%
“…Characterization of mRNA and protein expression in the liver tissues of Tibetan pigs remains to be performed. Recently, high-throughput sequencing of DNA, RNA, and proteins, has been widely used to study physiological processes and traits [9,10] in pigs.…”
Section: Introductionmentioning
confidence: 99%
“…The position of the variants was determined by reference to the Sus Scrofa genome (version 10.2). Total RNA was isolated from the endometrium of Meishan and Duroc pigs 72 days after onset of pregnancy, following procedures described in a previous study [ 8 , 42 ]. Primers are shown in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Nuclear factor-kappaB (NF-κB) as the key gene of NF-κB signaling, positively regulates the hyaluronan biosynthesis, which may explain the wrinkled skin and face of Meishan pigs (Zhao et al, 2018;Zhou et al, 2021). Previous research studying the protein expression patterns in endometrial tissue from Meishan and Duroc sows revealed that there were 114 differentially expressed proteins identified at day 49 and 98 differentially expressed proteins were identified at day 72 during pregnancy, suggesting that the differentially expressed proteins may be a major factor influencing the differences in embryonic loss between Meishan and Duroc sows during mid-gestation (Wang et al, 2019a). However, given the high complexity of reproduction performance and related phenotypes, the genetic basis of superior characteristics in Meishan pigs remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%